The August 2018 Kaktovik Earthquakes: Active Tectonics in Northeastern Alaska Revealed With InSAR and Seismology. Issue 24 (23rd December 2019) - Gaudreau, É.; Nissen, E. K.; Bergman, E. A.; Benz, H. M.; Tan, F.; Karasözen, E.
Abstract: The largest earthquakes recorded in northern Alaska ( M w 6.4 and M w 6.0) occurred ∼ 6 hr apart on 12 August 2018, in the northeastern Brooks Range. The earthquakes were captured by Sentinel‐1 interferometric synthetic aperture radar (InSAR) satellites and Earthscope Transportable Array seismic data, giving insight into the little‐known active tectonic processes of Arctic Alaska, obscured until recently by sparse data availability. In this study, InSAR modeling, teleseismic back projections, calibrated hypocentral relocations, and regional moment tensor solutions resolve two previously unknown, SSW dipping right‐lateral fault segments. These are the first active faults identified as conjugate to the NE trending sinistral Canning displacement zone directly to the west, which is therefore a more complex zone of diffuse faulting than previously thought. The northeastern Brooks Range has been characterized as an area of low to moderate seismic hazard, but these earthquakes illustrate the potential for larger, possibly destructive events in a region earmarked for rapid resource development. Plain Language Summary: The largest earthquakes recorded in northern Alaska (magnitude 6.4 and magnitude 6.0) occurred ∼ 6 hr apart on 12 August 2018. Few active faults are mapped in this region despite widespread seismicity, and the current tectonic setting remains unclear due to limited available data and the remote location. We use satellite radar images and seismic data to resolve two previously unknown fault segments, along which the magnitude 6.4 earthquake ruptured unilaterally eastward. This fault geometry demonstrates that the Canning displacement zone, the main tectonic feature in the area, is a more complex zone of diffuse faulting than previously thought. These results are also important for reassessing seismic hazard by illustrating the potential for damaging earthquakes on seemingly aseismic faults. Key Points: The largest earthquakes recorded in northern Alaska ( M w 6.4 and M w 6.0) occurred on previously unknown active faults InSAR and calibrated hypocenter relocations indicate that the faults are conjugate to the Canning displacement zone The Canning displacement zone involves a complex fault network and vertical‐axis block rotations